Methane production from food waste via mesophilic anaerobic digestion with ethanol pre-fermentation: Methanogenic pathway and microbial community analyses. (February 2020) - Zou, Hui; Gao, Ming; Yu, Miao; Zhang, Wenyu; Zhang, Shuang; Wu, Chuanfu; Tashiro, Yukihiro; Wang, Qunhui
Graphical abstract: Highlights: δ 13 C-Ethanol after ethanol pre-fermentation (EP) was studied. Acetotrophic pathway is still the main metabolism pathway (59.3%) after EP. EP caused the relative abundance of Clostridium increase by 7.6% than the control. Methanobacterium became the dominant species (58.9%) after EP. Abstract: To investigate the methanogenic pathway and microbial community in a mesophilic anaerobic digestion (AD) system with food waste (FW) ethanol pre-fermentation (EP), two semi-continuous AD systems were operated by feeding FW with (PSR) and without EP (control). In this study, δ 13 C-ethanol was supplemented as solo substrate for AD sludge when the reactors operation stabilized to analyze the methanogenic pathways. The results suggested that approximately 59.3% of methane was produced from acetotrophic methanogens, while 40.7% was formed by hydrogenotrophic methanogens in the PSR group. On the other hand, compared with control, methane produced via CO2 reduction pathway was increased by 4.70%. Meanwhile, the composition variations of the microbial community in AD supported the above conclusion, since the relative abundances of Clostridium and Methanobacterium were enhanced by 7.6% and 10.2%, respectively in PSR reactor. These results provided a theoretical basis for AD applications and biogas yield improvements with EP process.